Winter positions of Arctic front during periods of cooling and warming - A. Yu. Mikhailov; A. N. Zolotokrylin; T. B. Titkova (Лëд и снег, 2016)
Winter positions of the Arctic front (AF) during the known periods of the climate cooling (1949–1980) and warming (1981–2012) were analyzed within the sector 10° W – 60° E. The AF positios were determined by the following indicators: 1) a surface pressure; 2) horizontal wind divergence; 3) geostrophic vortex; 4) geostrophic heat advection. The main extrema of these four dynamic characteristics coincide and fall on the latitude 72.5° N. This corresponds to the average position of the AF for a given resolution and confirms correctness of our choice of these characteristics as the AF indicators. Relative differences between mean profiles of all values of the above warm and cold periods were calculated using method of normalization of each value for the corresponding latitude by the standard deviation for the entire period (1949–2012). To study variability of the AF position we used mean yearly winter profiles of the variables under investigation together with the statistical analysis of positions of the extrema within the latitude degrees. For pressure and geostrophic advection positions of the absolute minima were determined while for geostrophic vortex and divergence – positions of the absolute maxima. The data show that according to different criteria the AF average positions for the period 1949–2012 lie within the zone 72.4–73.4 N. The interannual variability of the AF positions lies within the 1–2 degrees of latitude and corresponds to the range of the air temperature variability above the zone of maximal changes in the sea ice area. According to the standard deviation values of the divergence and the geostrophic vortex are the most stable in region of the AF passage. Comparison of differences of the studied characteristics between the warm and cold periods shows that the changes in the AF positions are not statistically significant (P(t) < 91% t‑criterion) unlike the changes in positions of isolines which characterize the warming (P(t) = 100%). Thus, despite significant changes in properties of the surface and the temperature regime to the north of 72.5 N (the warming), according to all the criteria the AF climatic position remains quasi‑stationary for 32‑year periods of averaging.